(untitled) (Zaporizhzhia Historical Review, 2021)
The purpose of the paper is to reveal the general orientation and stages of politics of France concerning Zaporozhzhya and the Zaporozhian – Crimean relations in New Sich Times. The directions and methods of the French consuls’activity in the Crimea and its influence on the essence of Khan’s foreign policy are also elucidated.